2024
DOI: 10.3389/feduc.2024.1328769
|View full text |Cite
|
Sign up to set email alerts
|

The use of ChatGPT in teaching and learning: a systematic review through SWOT analysis approach

Duong Thi Thuy Mai,
Can Van Da,
Nguyen Van Hanh

Abstract: IntroductionThe integration of ChatGPT, an advanced AI-powered chatbot, into educational settings, has caused mixed reactions among educators. Therefore, we conducted a systematic review to explore the strengths and weaknesses of using ChatGPT and discuss the opportunities and threats of using ChatGPT in teaching and learning.MethodsFollowing the PRISMA flowchart guidelines, 51 articles were selected among 819 studies collected from Scopus, ERIC and Google Scholar databases in the period from 2022-2023.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Prior studies indicating that A.I. robots may increase student participation and discourse point to ChatGPT's persistent positive effect on classroom engagement (Ho, 2024;Javaid et al, 2023;Mai et al, 2024). According to research, students find utilizing ChatGPT to be more engaging while learning new words, writing, and language use (Pham & Nguyen, 2024).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies indicating that A.I. robots may increase student participation and discourse point to ChatGPT's persistent positive effect on classroom engagement (Ho, 2024;Javaid et al, 2023;Mai et al, 2024). According to research, students find utilizing ChatGPT to be more engaging while learning new words, writing, and language use (Pham & Nguyen, 2024).…”
Section: Discussionmentioning
confidence: 99%
“…tools, employing ChatGPT in the language learning classroom is an effective support tool for both teachers and students. However, Mai et al (2024) and Pham and Nguyen (2024) found that teachers have varying views on the use of ChatGPT in the classroom. While some are concerned about the effects on language learning and knowledge acquisition, others regard it as limitations for its accuracy and personalized learning (Pham & Nguyen, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Students' perceptions of ChatGPT as a digital co-teacher capture a range of sentiments, representing a complex interaction of anticipations, encounters, and worries. On the extreme end of the spectrum, some students view ChatGPT as a ground-breaking instrument that simpli es access to information and assistance (Yu, 2024;Mai et al, 2024). These students see it as a trustworthy ally in their academic endeavors and value its e ciency and convenience.…”
Section: Perceptions Of Chatgpt As a Digital Co-educatormentioning
confidence: 99%
“…This term was first introduced in 2008 by the United Kingdom Post Office, who conducted a survey on mobile phone usage and found that 53% of mobile phone users in Britain experienced stress when their mobile phones were inaccessible (Cinar et al, 2023). Since then, as society has become increasingly reliant on technology (Mai et al, 2024;Pan et al, 2024), nomophobia has emerged as a multifaceted psychological and cultural phenomenon with potential ramifications in mental health, including learning possibilities. Therefore, research on the prevalence of nomophobia among students has been proliferating, and a recent systematic review of 28 cross-sectional studies on the prevalence of nomophobia in 11,300 university students (Tuco et al, 2023) revealed that, overall, it was close to 100%.…”
Section: Introductionmentioning
confidence: 99%